2015
DOI: 10.1002/jcp.25100
|View full text |Cite
|
Sign up to set email alerts
|

RhoA‐Mediated Functions in C3H10T1/2 Osteoprogenitors Are Substrate Topography Dependent

Abstract: Surface topography broadly influences cellular responses. Adherent cell activities are regulated, in part, by RhoA, a member of the Rho-family of GTPases. In this study, we evaluated the influence of surface topography on RhoA activity and associated cellular functions. The murine mesenchymal stem cell line C3H10T1/2 cells (osteoprogenitor cells) were cultured on titanium substrates with smooth topography (S), microtopography (M), and nanotopography (N) to evaluate the effect of surface topography on RhoA-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Surface topography is recognized as an important factor for better osseointegration and regulation of cellular behavior. Recent studies showed that surface topography modulates some cellular behaviors such as cell morphology, RhoA activation and osteogenic differentiation 7) . Although recent studies have suggested that surface wettability modulated by surface treatments could enhance the early osseointegration process 21) , it remains to be determined how the modulated surface properties reciprocally interact and how they regulate cellular behavior.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Surface topography is recognized as an important factor for better osseointegration and regulation of cellular behavior. Recent studies showed that surface topography modulates some cellular behaviors such as cell morphology, RhoA activation and osteogenic differentiation 7) . Although recent studies have suggested that surface wettability modulated by surface treatments could enhance the early osseointegration process 21) , it remains to be determined how the modulated surface properties reciprocally interact and how they regulate cellular behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were seeded on D0 and D56 disks at a density of 2.0×10 4 cells/disk and cultured in α-MEM with 3% FBS for 6 h. To visualize cell morphology, the actin filaments were labeled with Texas Red-X phalloidin (Invitrogen, Grand Island, NY, USA) and the nuclei were counterstained with DAPI (Vectashield HardSet Mounting Medium, Thermo Fisher) as described in our previous study 7) . The stained cells were observed under a fluorescence microscope (BZ-9000, Keyence).…”
Section: Fluorescence Staining For Cell Morphology Analysismentioning
confidence: 99%
See 3 more Smart Citations